Investigation and Analysis on Employment of Chinese Undergraduate Graduates - Wang Wei; Shang Yixin (RIRAI Publisher, 2022)
This paper sorts out the data in the employment quality report of colleges and universities, and studies the employment structure, employment choice and reasons of graduates under the first round of